Creation and recreation: environmental benefits and human leisure - Rolston, Holmes, 1932-2025, author; Venture Publishing, Inc., publisher (Colorado State University. Libraries, 1991)
The way in which nature based recreation and preservation are inseparably entwined is suggested by the word creation embedded in the word recreation. We cannot live by leisure alone. But labor, industry, and business form only a part of our manifold human relations with nature. Nature as resource to work on should not preempt entirely these other relations that are also important. At work, one needs to be in the black, but at such leisure, one knows that the most important color on Earth is green. Natural wonders keep human life wonder full when humans keep a world full of such wonders, when the recreation also brings contact with the creation.
This article results from participation in a U.S. Forest Service symposium on the benefits of outdoor recreation, Snowbird, Utah, May, 1989.
Keywords: leisure; creation; natural wonders; values in nature; non-economic value; outdoor recreation